Political Ecology on Instagram Digital Media as A Politeness Branding Image - Mazida Fadhila (EDP Sciences, 2021)
The convergence of technology has a major impact on human life. The dependence on media forms media ecology. Media ecology becomes a bridge in creating a group self-image. The main study of this research was to analyze the forms of politeness verbal messages on digital media @PandemicTalks. The Instagram account @PandemicTalks presents a new style of sharing information on digital media through graphic and visual content. The research orientation focused on visual verbal messages with the substance of COVID-19 related to the government policies. This qualitative research used both netnographic and descriptive phenomenological method. The results show that the COVID-19 Pandemic formed the characters of technology literate society. The communication lines were more dynamically interactive. Language was as a social and political control in creating the politeness branding image. The politeness strategy used the verbal wisdom markers. The sharing function politeness of visual verbal messages on the @PandemicTalks account was more dominant. The branding image used a persuasive euphemistic language style.